Defining Digital Excellence: Requisite Skills and Policy Implications for Digital Transformation - Mattias Wiggberg; Jan Gulliksen; Asa Cajander; Arnold Pears (IEEE Access, 2022)
The skills required to realise the potential of technological transformation to preserve humanity and our fragile world ecosystem in the next decade will centre on the development of digital solutions. This paper discusses the issue of characterising these competencies, since a definition is needed in order to ensure an adequate supply of cutting-edge scholars and a highly educated and agile technological workforce. The paper takes a mixed methods approach combining insights distilled from a rapid literature review, with interviews with leading practitioners and industry leaders. The validity and reliability of the results have been ensured through expert workshops and focus groups. The outcome is a robust definition of what digital excellence entails as well as a road map guiding educational policy and the future supply of digital excellence in national workforces.